Star Formation Rate of the Low Redshift Dwarf Galaxies J080947.50+213717.2 and J151839.94+220514.4 - Gautam, S. P.; Silwal, A.; Sedain, A.; Aryal, B. (Journal of Nepal Physical Society, 2021)
We performed a spectroscopic analysis of two low redshift dwarf galaxies, SDSSJ080947.50+213717.2, and SDSSJ151839.94+220514.4 selected from a catalogue of Paudel et al. 2018. The strong emission lines of the SDSS spectra of both galaxies were studied and the elements responsible were identified for those characteristic lines. The line ratio between Hα and Hβ (Hα/ Hβ) for the galaxies SDSSJ080947.50+213717.2 and SDSSJ151839.94+220514.4 was found to be 2.77 and 2.75, respectively, suggesting these are nearly dust free and star forming galaxies.. The star formation rate of the galaxies SDSSJ080947.50+213717.2 and SDSSJ151839.94+220514.4 was found to be 0.0232 M☉yr-1 and 0.05221 M☉yr-1, respectively. The ratio between NII and Hα was used to calculate the emission line metallicity, which was found to be 8.13 dex and 8.46 dex for the galaxies SDSSJ080947.50+213717.2 and SDSSJ151839.94+220514.4, respectively. From the comparison of our findings with the previous studies, slightly lower star formation rate than normal galaxies were noticed. The metallicity value for both of the galaxies were positioned in the group of low-surface-brightness galaxies of Bargvell’s dwarfs..